Gallery Walk Technique to Improve Students’ Speaking Skill - M. Arif Rahman Hakim; Nike Anggraini; Andri Saputra (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This study aims to overcome some problems of students’ speaking ability at the Second Grade Students of Senior High School 6 Bengkulu Tengah, Bengkulu, Indonesia by using gallery walk technique. The participants of this study were 30 students. The method used in this study was Classroom Action Research (CAR). This study was carried out in two cycles. Each cycle consisted of four meetings. Each cycle consisted of four stages-planning, action, observing and reflecting. The result of this study showed that the students’ speaking ability was improved after the action was given to the students. Besides, using gallery walk technique could motivate the students to speak up confidently and also could make the students became more active and enjoy in learning process at the classroom. Most of the students gradually gained good scores at the end of the cycle. The minimum score of Mastery Criterion- Kriteria Ketuntasan Minimal (KKM) of English subject was 71 (seventy-one). In cycle I, the result of the students’ score was failed, where the mean score of the students was 70.29 (poor). However, in cycle II, the result of the cycle showed that there was good improvement. The students’ mean score in this stage was 80.83 (very good). In conclusion, gallery walk technique could improve students’ speaking ability.